Environmental impact of mine water, utilization and management in Indian mines - Shirin S.; Jamal A. (My University, 2025)
Mine water in coal mines is a common problem and its availability increases with depth. The disposal of wastewater from mines is one among the most important problems associated with coal mining operations. As a result of mining, both quality and quantity of water are severely affected. The paper has been conducted to assess the quality of water sump and its subsequent utilization in mines and other purposes. It may be concluded from the above study that the pH, TDS, and TSS of water is varying from one point to another point along with other objectionable parameters. Until recently all pollution abatement efforts are aimed at controlling mine wastewater discharge into receiving waters. This paper focused on utilization and management of mine water treatment also. © RASĀYAN. All rights reserved.